Development of graphene materials and phthalocyanines for application in dye-sensitized solar cells - Chindeka, Francis (Rhodes University, Faculty of Science, Department of Chemistry, 2020)
Two sets of dye-sensitized solar cells (DSSCs) were fabricated. In the first set, dye-sensitized solar cells (DSSC) were fabricated by incorporating graphene materials as catalysts at the counter electrode. Platinum was also used as a catalyst for comparative purposes. Different phthalocyanines: hydroxyl indium tetracarboxyphenoxy phthalocyanine (1), chloro indium octacarboxy phthalocyanine (2) and dibenzoic acid silicon phthalocyanine (3) were used as dyes. Complex 3 gave the highest power conversion efficiency (Î·) of 3.19% when using nitrogen doped reduced graphene oxide nanosheets (NrGONS) as a catalyst at the counter electrode, and TiO2 containing rGONS at the anode. The value obtained is close to 3.8% obtained when using Pt catalyst instead of NrGONS at the cathode, thus confirming that NrGONS is a promising candidate to replace the more expensive Pt. The study also shows that placing rGONS on both the anode and cathode improves efficiency. In the second set, DSSCs were fabricated by using 2(3,5-biscarboxyphenoxy), 9(10), 16(17), 23(24)-tri(tertbutyl) phthalocyaninato Cu (4) and Zn (5) complexes as dyes on the ITO-TiO2 photoanodes containing reduced graphene oxide nanosheets (rGONS) or nitrogen-doped rGONS (NrGONS). The evaluation of the assembled DSSCs revealed that using ITO-TiO2-NrGONS-CuPc (4) photoanode had the highest fill factor (FF) and power conversion efficiency (É³) of 69 % and 4.36 % respectively. These results show that the asymmetrical phthalocyanine complexes (4) and (5) showed significant improvement on the performance of the DSSC compared to previous work on symmetrical carboxylated phthalocyanines with É³ = 3.19%.
Keywords: Dye-sensitized solar cells; Graphene; Phthalocyanines; Molecular orbitals; Impedance spectroscopy